Understanding the Risk Factors, Burden, and Interventions for Chronic Respiratory Diseases in Low- and Middle-Income Countries: A Scoping Review - Perla Boutros; Nour Kassem; Valentin Boudo; Valentin Boudo; Ali Sié; Ali Sié; Stephen Munga; Stephen Munga; Martina A. Maggioni; Martina A. Maggioni; Martina A. Maggioni; Marcin Golec; et al. (Frontiers Media S.A., 2024)
ObjectiveThis scoping review aims to identify risk factors for COPD and asthma, examine the burden and intervention measures, and clarify the findings in the context of climate change, with a particular focus on LMICs.MethodsFollowing the PRISMA-ScR guidelines, we conducted a scoping review using PubMed, Embase, and Scopus, focusing on studies published from 2011 to 2024.ResultsOur review included 52 studies that encompassed 244,004 participants. Predominantly conducted in SSA (n = 43, 83%) and Asia (n = 16, 31%), they address indoor and ambient air pollution, occupational hazards, and environmental conditions. Climate change exacerbates risks, varying regionally. SSA faces severe household and occupational exposures, while other LMICs deal with industrial and urban pollution. Stigma, social exclusion and economic burden underscore the necessity for intervention strategies (e.g., educational programs, pulmonary rehabilitation, low-emission cookstoves).ConclusionOur research shows a strong link between air pollution, occupational and environmental exposures, and the prevalence of COPD and asthma in LMICs. It suggests that targeted interventions are effective ways to mitigate these diseases and also highlights the significant impact of climate change on respiratory health.